Social connectedness and fragility of social capital: view from an Orissa village - Mohapatra, Bishnu N. (2001)
Social capital is in a way fundamentally about `connectedness' or engagements - especially those that contribute in building trust among people, increase the predictability of their behaviour and promote collective action. The author seeks to explore the associations and interactions that give rise to such engagements - by locating his search in a small village in Orissa's Puri district. Here collective memory and its role in conflict resolution in the village is crucial in creating or destroying trust. Memory, among other things, holds the key for the continuation of social connectedness or engagements. - Reproduced
Keywords: Infrastructure development - India - Orissa; Social capital - India; Social capital